The Effect of Information Systems, Information Technology and Organisational Culture on Performance - Sumaryono, Sumaryono; Ali, Hapzi (Dinasti Publisher, 2023)
Literature Review Article The Effect of Information Systems, Information Technology and Organisational Culture on Performance is a scientific article that aims to build a research hypothesis of the influence between variables that will be used in further research, within the scope of Human Resource Management science. The method of writing this Literature Review article is by library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this literature review article are: 1) Information systems affect performance; 2) Information Technology affects performance; and 3) Organisational Culture affects performance.